The Influence of Work Life Balance and Work Motivation on Employee Job Satisfaction in the Capital Expenditure and Operational Expenditure Departments of PT Bio Farma (Persero) Bandung - Eka Sartika; Khaerul Rizal Abdurahman (SAFE-Network, 2026)
Employee job satisfaction is an important aspect that reflects employees’ attitudes and evaluations of their work. Attendance data for 2024 show fluctuations in the level of employee tardiness in the Capital Expenditure and Operational Expenditure Operational Department, indicating that job satisfaction has not been consistently established. Improving employee job satisfaction can be achieved through effective management of work-life balance and support for work motivation. This study aims to examine the effect of work-life balance and work motivation on employee job satisfaction in the Capital Expenditure and Operational Expenditure Operational Department of PT Bio Farma (Persero) Bandung. This research uses a quantitative approach with multiple regression analysis methods. In addition, descriptive analysis is used to describe the conditions of work-life balance, work motivation, and employee job satisfaction based on respondents’ perceptions. Prior to hypothesis testing, the research data were first tested using classical assumption tests to ensure the feasibility of the regression model employed. The research respondents consisted of 30 employees, with data processing conducted using IBM SPSS Statistics version 27. The results indicate that partially, work-life balance has a positive effect on employee job satisfaction, and work motivation also has a positive effect on employee job satisfaction. Furthermore, simultaneously, work-life balance and work motivation have a significant impact on employee job satisfaction. The implications of this study are expected to serve as a basis for management in formulating policies to improve work-life balance and strengthen motivation in order to enhance employee job satisfaction sustainably.